TH5.4 Robustness of morbidity and mortality documentation before emergency laparotomies. (9th August 2022) - Muehlschlegel, Charlotte; Rees, Chantal; Borgas, Pia; Taheem, Muhesh; Bedwani, Nader; Kalidindi, Venugopala; Bhanot, Kunal
Abstract: Introduction/Aims: Participation in the National Emergency Laparotomy Audit (NELA) is a national requirement, highlighting areas for improvement in patient care and service provision . When consenting for emergency laparotomy, NELA Morbidity and Morality scores (NMMS) should be clearly documented, informing the consent process and guiding surgical intervention. Aims: Calculate the incidence of clear NMMS documentation Compare incidence to national standards Provide education regarding national standards and importance of NMMS documentation Introduce a consent form supplement, prompting NMMS documentation Ascertain intervention success Method: A retrospective (C1) (13/02/21–06/07/2021) and ongoing prospective (C2) (24/10/2021-present) analysis of emergency laparotomies in our local hospital was performed before and after implementation of interventions respectively. Laparotomies were categorised by operation time, NMMS documentation time, patient age and gender. Results were presented locally. Interventions included departmental education and a bright orange supplementary sticker placed on consent forms, providing fields for NMMS documentation. Fischer's exact t-test was used to calculate p values. Results: 30 and 21 patients were included in C1 and C2 respectively. More patients had clear NMMS documentation in C2 (10/30 vs 16/21; p<0.005). Within C2, sticker use was associated with more frequent NMMS documentation (7/7 vs 8/13; p=0.1107). Conclusion: Use of NMMS informs consent, guides surgical decision making and improves accountability. Whilst important for both legal and governance reasons, utilisation and documentation of clinical decision-making tools whilst managing unwell patients can be onerous. We found combining both education and a visual adjunct has improved compliance with the NMMS documentation NELA standards.